Characterizing the potential environmental risks of South African coal processing wastes - Moyo, Annah (Centre for Bioprocess Engineering Research, 2019)
The environmental impacts of coal processing wastes are a challenge in South Africa as large amounts of coal wastes are produced annually, pegged at 60 million tons per year according to Eberhard (2011). Whilst the fossil fuel-based industry is in decline globally, coal is likely to remain the dominant source of power in South Africa. The major environmental impacts reported in several studies are water pollution and soil quality degradation due to acid rock drainage (ARD) and its associated elevated levels of elements and salts. Several studies have shown the environmental performance of the wastes to be dependent on the geochemical properties of the wastes. Owing to the complex nature of coal wastes, their characterisation using tools developed for hard rock ores is associated with inconsistency and uncertainty. As a result, the South African coal processing wastes are poorly characterized and the associated risks not well understood. This study investigates the reliability of relevant characterisation techniques and interpretation of characterisation data in terms of the environmental risk potential of coal wastes. The outcomes of the study address some of the uncertainties and deficiencies arising from the current characterisation tools and evaluate potential environmental risks posed by coal processing wastes. Laboratory-scale characterisation of the physio-chemical properties and of ARD and elemental risk potential of two ultrafine coal waste and one discard waste sample were conducted. Evaluation of accuracy and repeatability of selected analyses was conducted on a certified coal standard. The selected analyses tested for accuracy and repeatability were total sulphur analysis by Leco and Eschka methods in addition to elemental analysis by wavelength dispersive x-ray fluorescence (WDXRF), inductively coupled plasma mass spectrometry (ICP-MS), inductively coupled plasma atomic emission spectroscopy (ICP-AES) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The ISO 157:1996 and ACARP C15034 protocols for assessment of sulphur forms were also compared and evaluated for precision using the coal standard and coal waste samples. Conversions of the sulphur species under static ARD tests were also studied to understand the sulphur species behaviour and implication on ARD potential. The mineralogy of the coal wastes was evaluated from a quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN) and quantitative x-ray diffraction (QXRD) analysis. In addition, conventional net acid generating (NAG) and acid-base accounting (ABA) static tests were enhanced through extended boil NAG tests to assess the organic acids effect on the NAG capacity. The static tests were validated by theoretical ARD calculated from mineralogy as well as biokinetic shake flask tests which gave the timerelated acid generating behaviour of the coal waste samples. Sequential chemical extractions combined with a simple score and ranking protocol were subsequently used to evaluate the potential water and soil-related risks associated with environmentally available elements and salts in the coal wastes. The results showed both the Leco and Eschka methods to be highly precise (±0.01-0.03 % standard error) but the Leco was more accurate (±3.1 % compared to ±12.5 % relative standard error (RSE)). The total sulphur content of the coal processing waste was less than 2 %. The ISO157:1996 and ACARP C15034 protocols gave comparable and slightly different results but the latter was more precise in sulphate analysis. Furthermore, the ACARP protocol could differentiate the acid forming sulphates from the soluble sulphates giving a better theoretical maximum acid producing potential. The sulphur species from the two chemical methods and QEMSCAN mineralogy showed 52-61 %, 12-26 % and 21-43 % to be sulphide, sulphate and organic/low-risk sulphur respectively. The conversion of the sulphur species showed that partial solubilisation of sulphides in ANC and partial conversion of organic/low-risk sulphur under NAG tests can cause an over or underestimation of ARD potential. The static ARD tests has shown the Witbank coal discards sample to be potentially acid forming (PAF) (9.2-25.9 kg H2SO4/Ton), Waterberg coal slurry to be non-acid forming (NAF) (-68.6 to -46.8 kg H2SO4/Ton) and Witbank coal slurry to be uncertain (-12.1 to 9.9 kg H2SO4/Ton). The extended boil NAG tests showed organic acids effect on the Witbank coal slurry likely caused an overestimation of the NAG capacity. Validation of the static tests by biokinetic tests and ARD calculated from mineralogy classified both Witbank samples as PAF and the Waterberg sample as NAF. The results also showed the net acid producing potential of the coal wastes to depend on the mineralogy of the samples. The elemental results showed WDXRF and LA-ICP-MS analysed most of the elements accurately within ±10 % RSE and that a combination of techniques provides more reliable and accurate results. The analyses showed the coal waste to contain significant amounts of environmentally sensitive elements like Cr, As, Mo, Sb, Se. The ranking and scoring of potentially available elements under oxidising leach conditions evaluated Fe in Waterberg coal slurry and Witbank coal discards to pose high risk in drinking water while S (as sulphate), Pb, Sb, Mn, As, Al and Hg in the three samples pose moderate risk. This case study evaluated the accuracy and precision of commonly used analytical techniques and applicability of risk evaluation protocols for coal processing wastes. The research outcomes underlined some factors that cause uncertainty and inconsistency with the evaluation of ARD potential of coal wastes. The findings highlighted the need to validate and complement the characterisation data using various tools and risk evaluation protocols to overcome specific limitations. The results also indicated the coal wastes have the potential to cause environmental impacts from ARD and elevated concentration of elements and salts, thus providing a basis for designing and implementing waste management strategies which minimise these risks. The mineralogy and elemental composition of coal wastes showed enrichment of elements and presence of potentially usable and economically valuable constituencies for future studies on value recovery. Characterisation of coal processing wastes for air pollution impacts is recommended for future studies as well as a study of ARD behaviour under continuous flow systems to more closely represent the conditions in dump disposal scenario.